Histological and scanning electron microscope observations on the developing retina of the cuttlefish (Sepia officinalis Linnaeus, 1758) - Arias-Montecino, Alejandro (2024)
In this work we present a detailed study of the major events during retinal histogenesis of the cuttlefish Sepia officinalis from early embryos to newly hatched animals and juveniles. For this purpose, we carried out morphometric and histological analyses using light and scanning electron microscopy. From St19, the first embryonic stage analysed, to St23/24 the embryonic retina is composed of a pseudostratified epithelium showing abundant mitotic figures in the more internal surface. At St24 the first photoreceptor nuclei appear in the presumptive inner segment layer, while an incipient layer of apical processes of the future rhabdomeric layer become visible at St25. From this stage onwards, both the rhabdomeric layer and the inner segment layer increase in size until postnatal ages. In contrast, the width of the supporting cell layer progressively decreases from St25/26 until postnatal ages. S. officinalis embryos hatched in a morphologically advanced state, showing a differentiated retina even in the last stages of the embryonic period. However, features of immaturity are still observable in the retinal tissue during the first postnatal weeks of life, such as the existence of mitotic figures in the apical region of the supporting cell layer and migrating nuclei of differentiating photoreceptors crossing the basal membrane to reach their final location in the inner segment layer. Therefore, postnatal retinal neurogenesis is present in juvenile specimens of S. officinalis.